A critical evaluation of the reintegration experiences of child sex offenders in the community - Woodward, Darren (2018)
Criminology has conventionally focussed on the onset and punishment of crime. Less attention is paid to how offenders reintegrate, exist, cope and move away from crime. However, there is a growing body of research interested in reintegration and desistance from crime. The literature on sex offender reintegration and desistance is limited but emerging, with studies exclusively involving child sex offenders remaining scarce. Therefore, this thesis has been designed to evaluate the reintegration experiences of child sex offenders in a community in England and Wales. Using a qualitative, semi-structured, individual interview approach, data were collected from 10 men (the participants) who had at least one current and at least one previous child sexual offence conviction. The index offences ranged from internet related charges, to rape. Data were additionally obtained from 11 professionals working with child sex offenders in the community. The professionals worked for either the National Probation Service (NPS), the police or Circles of Support and Accountability (COSA). The themes of resettlement, risk management and stigma were discussed, and an illustrative model of child sex offender reintegration was developed. The findings suggest the participants were vulnerable. They shared experiences of verbal and physical abuse at the hands of non-sex offenders, loss, fear, isolation and pressure. They were not afforded the opportunities to reintegrate with success in comparison to other offender types, with internet offenders’ opportunities being lessened further. They used a variety of coping methods, including self-risk management, identity passing, avoidance and appropriate offence disclosure. In addition, the illustrative model highlighted how the men were active agents of their reintegration journey, rather than being passive. They shaped and negotiated their way through life in the community as men with child sexual offences in different and interesting ways, whilst being mindful of the stigma associated with this offence type.
HydraID: hull:16593 ETD Collection: ETDCriminology
Keywords: Criminology